Recurrent herpes zoster with segmental paresis and postherpetic neuralgia - Martić, Vesna (Vojnosanitetski pregled, 2014)
Introduction. Postherpetic neuralgia and segmental paresis represent rare complications of herpes zoster infection. Recurrent herpes zoster is also rare and occurs within the first 3 years of the begining of the illness in only 1.4% of cases but it is generally higher in cases of chronic lymphatic leukemia (3.5%). Case report. We presented a patient with lymphatic leukemia who during the remission had 3 episodes of herpes zoster over a year. All of them took diffrent parts of the body. One of these episodes was complicated by postherpetic neuralgia and segmental paresis. A complete recovery was seen in all the three episodes. Conclusion. As immunosuppression is one of mechanisms of virus reactivation, it is likely associated with the described rare complications of herpes zoster.
Keywords: herpes zoster; leukemia; lymphocytic; chronic; b-cell; comorbidity; paresis; neuralgia; drug therapy